Hydrolytic Profile of the Culturable Gut Bacterial Community Associated With Hermetia illucens - Callegari, Matteo; Jucker, Costanza; Fusi, Marco; Leonardi, Maria Giovanna; Daffonchio, Daniele; Borin, Sara; Savoldelli, Sara; Crotti, Elena (Frontiers in Microbiology, 2020)
Larvae of the black soldier fly (BSF) Hermetia illucens (L.) convert organic waste into high valuable insect biomass that can be used as alternative protein source for animal nutrition or as feedstock for biodiesel production. Since insect biology and physiology are influenced by the gut microbiome, knowledge about the functional role of BSF-associated microorganisms could be exploited to enhance the insect performance and growth. Although an increasing number of culture-independent studies are unveiling the microbiota structure and composition of the BSF gut microbiota, a knowledge gap remains on the experimental validation of the contribution of the microorganisms to the insect growth and development. We aimed at assessing if BSF gut-associated bacteria potentially involved in the breakdown of diet components are able to improve host nutrition. A total of 193 bacterial strains were obtained from guts of BSF larvae reared on a nutritious diet using selective and enrichment media. Most of the bacterial isolates are typically found in the insect gut, with major representatives belonging to the Gammaproteobacteria and Bacilli classes. The hydrolytic profile of the bacterial collection was assessed on compounds typically present in the diet. Finally, we tested the hypothesis that the addition to a nutritionally poor diet of the two isolates Bacillus licheniformis HI169 and Stenotrophomonas maltophilia HI121, selected for their complementary metabolic activities, could enhance BSF growth. B. licheniformis HI169 positively influenced the larval final weight and growth rate when compared to the control. Conversely, the addition of S. maltophilia HI121 to the nutritionally poor diet did not result in a growth enhancement in terms of larval weight and pupal weight and length in comparison to the control, whereas the combination of the two strains positively affected the larval final weight and the pupal weight and length. In conclusion, we isolated BSF-associated bacterial strains with potential positive properties for the host nutrition and we showed that selected isolates may enhance BSF growth, suggesting the importance to evaluate the effect of the bacterial administration on the insect performance.